A Study On Employees Perception Of Commercial Banks Towards Performance Appriasal System In Thiruvarur District (International Journal of Food and Nutritional Sciences, 2022)
Business companies pay considerable value to human capital because human resources are the primary sources of strategic gain and have the potential to turn all other resources into goods or services. The study of performance Appriasal is very essential for all organisations and the banking sector is no exception, particularly in the current situation of financial recession. The Present study focuses on the clarification of employees' understanding of the performance Appraisal system in the district of Thiruvarur. Current research papers provide opportunities for scale production of Performance Appraisal elements, balanced scorecard and employee satisfaction & retention and employment participation performance.